SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PELATIHAN PENGGUNAAN ALAT PERTANIAN BERBASIS IOT DENGAN METODE ARAS - Adam Wirayuda; Angga Putra Juledi; Ibnu Rasyid Munthe (Politeknik Bisnis Indonesia, 2023)
The potential benefits of using IoT technology-based tools in agriculture are large, but implementation is still hampered by farmers' lack of understanding. Therefore, training was carried out taking into account the different conditions and needs of farmers in the Bagan Sinembah area. This research aims to build a Decision Support System (DSS) using the ARAS method in determining training priorities for using Internet of Things (IoT)-based agricultural equipment for farmers in the Bagan Sinembah area. Criteria for determining training priorities involve factors such as infrastructure availability, level of technological understanding, local topographic conditions, scale of agricultural business, and availability of funds and resources. The research results obtained consist of 3 groups of farmers who will receive the highest training priority, namely: alternative KTA8 in the first position with a result of 0.85821, alternative KTA4 in the second position with a result of 0.83197, and alternative KTA7 in the third position with a result 0.82643. The highest priority is given to farmer groups with the highest yields. The research results show that the system built can help make it easier for the Faculty of Science and Technology, Labuhanbatu University, to make decisions regarding training priorities for farmers. The results of this research can contribute to the development of a decision support system to increase the efficiency and effectiveness of farmer training in using IoT technology in agriculture in the Bagan Sinembah area.